Microsatellite marker diversity in common bean (Phaseolus vulgaris L.) - Blair, Matthew W.; Giraldo Zapata, Martha C.; Buendía Castellanos, Hector F.; Tovar Luque, E.; Duque E., Myriam Cristina; Beebe, Stephen E. (Springer, 2006)
A diversity survey was used to estimate allelic diversity and heterozygosity of 129 microsatellite markers in a panel of 44 common bean (Phaseolus vulgaris L.) genotypes that have been used as parents of mapping populations. Two types of microsatellites were evaluated, based respectively on gene coding and genomic sequences. Genetic diversity was evaluated by estimating the polymorphism information content (PIC), as well as the distribution and range of alleles sizes. Gene-based microsatellites proved to be less polymorphic than genomic microsatellites in terms of both number of alleles (6.0 vs. 9.2) and PIC values (0.446 vs. 0.594) while greater size differences between the largest and the smallest allele were observed for the genomic microsatellites than for the gene-based microsatellites (31.4 vs. 19.1 bp). Markers that showed a high number of alleles were identified with a maximum of 28 alleles for the marker BMd1. The microsatellites were useful for distinguishing Andean and Mesoamerican genotypes, for uncovering the races within each genepool and for separating wild accessions from cultivars. Greater polymorphism and race structure was found within the Andean gene pool than within the Mesoamerican gene pool and polymorphism rate between genotypes was consistent with genepool and race identity. Comparisons between Andean genotypes had higher polymorphism (53.0%) on average than comparisons among Mesoamerican genotypes (33.4%). Within the Mesoamerican parental combinations, the intra-racial combinations between Mesoamerica and Durango or Jalisco race genotypes showed higher average rates of polymorphism (37.5%) than the within-race combinations between Mesoamerica race genotypes (31.7%). In multiple correspondance analysis we found two principal clusters of genotypes corresponding to the Mesoamerican and Andean gene pools and subgroups representing specific races especially for the Nueva Granada and Peru races of the Andean gene pool. Intra population diversity was higher within the Andean genepool than within the Mesoamerican genepool and this pattern was observed for both gene-based and genomic microsatellites. Furthermore, intra-population diversity within the Andean races (0.356 on average) was higher than within the Mesoamerican races (0.302). Within the Andean gene pool, race Peru had higher diversity compared to race Nueva Granada, while within the Mesoamerican gene pool, the races Durango, Guatemala and Jalisco had comparable levels of diversity which were below that of race Mesoamerica.